2014
DOI: 10.1021/mz500541w
|View full text |Cite
|
Sign up to set email alerts
|

Facile Assembly Enhanced Spontaneous Fluorescent Response of Ag+ Ion Containing Polyelectrolyte Multilayer Films

Abstract: Fluorescent organic−inorganic composite materials exhibiting "turn-on" response are often based on conjugated small molecules. Conjugated polymers, however, often exhibit a "turn-off" response in combination with metal ions. Here we present fluorescent turn-on behavior of a branched poly(ethylene imine)-poly(acrylic acid)-Ag + ion complex in a thin film. The material is characterized by UV−vis, spectrofluorometry, XPS, and ICP-MS. The turn-on response is exhibited only with all three components present, implyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…6,13,14 Additionally, silver ions in the PAH/PAA multilayers show a redox property with reducing agents and are reported to be reduced to silver nanoparticles in previous studies. 42,44,46 Therefore, because silver ions in the PAH/PAA LbLfilm showed a redox property with a reducing material, the silver ions in (PAH/PAA) 7 multilayers were reduced to silver nanoparticles by AA after immersion of the filter paper with (PAH/PAA) 7 multilayers containing silver ions into the AA solution. After preparation of silver nanoparticles on the surface of the filter paper, the color of the filter paper was changed to yellow or dark brown by the LSPR scattering of the silver nanoparticles.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,13,14 Additionally, silver ions in the PAH/PAA multilayers show a redox property with reducing agents and are reported to be reduced to silver nanoparticles in previous studies. 42,44,46 Therefore, because silver ions in the PAH/PAA LbLfilm showed a redox property with a reducing material, the silver ions in (PAH/PAA) 7 multilayers were reduced to silver nanoparticles by AA after immersion of the filter paper with (PAH/PAA) 7 multilayers containing silver ions into the AA solution. After preparation of silver nanoparticles on the surface of the filter paper, the color of the filter paper was changed to yellow or dark brown by the LSPR scattering of the silver nanoparticles.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%
“…The layer-by-layer (LbL) self-assembly technique is a useful method for fabricating uniform and thickness-controllable polyelectrolyte films on various substrates through the adsorption of alternating polyanions and polycations by electrostatic force and can be widely applied to chemical sensors for the detection of various chamicals. Recently, a LbL film containing a metal ion by coordination of the metal ion and polyelectrolytes has been reported. In these films, we reported a novel method to fabricate poly­(allylamine hydrochloride) (PAH) and poly­(acrylic acid) (PAA) LbL multilayers containing metastable metal ions through coordination between the amine groups of PAH and metal ions . These coating films have been applied for various applications, such as slippery film and gas sensors, by using the redox property of the metal ion contained in PAH/PAA LbL multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces also perform well in preventing microbial adhesion. Yin and coworkers incorporated silver nanoparticles into a PEI/PAA LbL matrix to further enhance the antibiofouling property of the superhydrophobic coating. This superhydrophobic fluorinated multilayer can efficiently prevent microbes (such as sulfate‐reducing bacteria Desulfovibrio salexigens , SRB) from adhering over the course of a week.…”
Section: Extrafunctionalitiesmentioning
confidence: 99%
“…Typically, the films are made of two oppositely charged polyelectrolytes or colloidal materials bound together through electrostatic interactions, assembled with a sequential dipping or spraying process . Exploring the functionalities of LbL films is a highly active research area, incorporating a broad range of materials (including polymers, nanoparticles, metal ions, lipids, proteins, dye molecules, dendrimers, and quantum dots) using various substrates. These materials are assembled not only with electrostatic interactions but also with hydrogen bonding, hydrophobic interactions, coordination interactions, covalent bonding, hydrophobic interactions, and complementary based pairing .…”
Section: Introductionmentioning
confidence: 99%
“…PEMs can be used to easily control the properties of arbitrary substrate surfaces; such properties include the hydrophobicity-hydrophilicity, charge properties, and morphology 25 . Hence, PEMs have been widely applied in the environmental, biomedical, and sensor fields 26 27 . Previously, we demonstrated that PEMs could easily control the protein adsorption properties, including the adsorption capacity and adsorption type from a mixed solution, via electrostatic interactions between the protein and the PEM surface 28 29 30 .…”
mentioning
confidence: 99%